The Effect Of Audit Committee Characteristics On Earnings Management: A Case Study Of Non-Financial Bumn Companies In Indonesia For The Period 2018-2022 - Vania Amanda; Fajar Gustiawaty; Retno Yuni Nur Susilowati; Ade Widiyanti (UNIVED Press, 2024)
This study aims to further investigate the effect of audit committee characteristics on earnings management practices, as measured by earnings management, in non-financial state-owned companies. This research uses quantitative methodology and data sources are obtained from secondary data. This analysis technique uses multiple regression analysis techniques, classical assumption tests and hypothesis testing, the data observations used in this study were 55. The findings of this study indicate the results of the study that audit committee activity has no significant effect on earnings management so that H1 is not supported, the audit committee size variable shows the results of a significant negative effect on earnings management so that H2 is supported, In line with H1, audit committee competence has no significant effect on earnings management so that H3 is not supported.